Voltage sensor current, SR Ca2+ release, and Ca2+ channel current during trains of action potential‐like depolarizations of skeletal muscle fibers - Hugo Bibollet; Elton L. Nguyen; Daniel R. Miranda; Christopher W. Ward; Andrew A. Voss; Martin F. Schneider; Erick O. Hernández‐Ochoa (Physiological Reports, 2023)
Abstract In skeletal muscle, CaV1.1 serves as the voltage sensor for both excitation‐contraction coupling (ECC) and L‐type Ca2+ channel activation. We have recently adapted the technique of action potential (AP) voltage clamp (APVC) to monitor the current generated by the movement of intramembrane voltage sensors (IQ) during single imposed transverse tubular AP‐like depolarization waveforms (IQAP). We now extend this procedure to monitoring IQAP, and Ca2+ currents during trains of tubular AP‐like waveforms in adult murine skeletal muscle fibers, and compare them with the trajectories of APs and AP‐induced Ca2+ release measured in other fibers using field stimulation and optical probes. The AP waveform remains relatively constant during brief trains (<1 sec) for propagating APs in non‐V clamped fibers. Trains of 10 AP‐like depolarizations at 10 Hz (900 ms), 50 Hz (180 ms), or 100 Hz (90 ms) did not alter IQAP amplitude or kinetics, consistent with previous findings in isolated muscle fibers where negligible charge immobilization occurred during 100 ms step depolarizations. Using field stimulation, Ca2+ release did exhibit a considerable decline from pulse to pulse during the train, also consistent with previous findings, indicating that the decline of Ca2+ release during a short train of APs is not correlated to modification of charge movement. Ca2+ currents during single or 10 Hz trains of AP‐like depolarizations were hardly detectable, were minimal during 50 Hz trains, and became more evident during 100 Hz trains in some fibers. Our results verify predictions on the behavior of the ECC machinery in response to AP‐like depolarizations and provide a direct demonstration that Ca2+ currents elicited by single AP‐like waveforms are negligible, but can become more prominent in some fibers during short high‐frequency train stimulation that elicits maximal isometric force.